Switching Metaphors / Palitan ng Talinghaga / At the Precipice / Two Sides of a Mirage / The Chore of Beauty / In Crowded Buses / Crowded Out Self / Woman: Talent and Tragedy - de Guzman, Sylvia O. (Review of Women's Studies, 1996)
---